Changes in glomerular filtration rate in young adults: population data - N. A. Kovalkova; A. D. Khudyakova; L. V. Shcherbakova; E. A. Vaskina; D. V. Denisova; Yu. I. Ragino; M. I. Voevoda (Сибирский научный медицинский журнал, 2020)
Aim of the study was to investigate glomerular filtration rate in population of 25–45 years old young people of Novosibirsk city. Material and methods. A survey of Novosibirsk typical district’s population has been carried out by the Institute of Internal and Preventive Medicine since 2013 to 2016. 1074 people (467 males and 607 females of 25–45 years old) have been included into the survey. The levels of glomerular filtration rate (GFR) were chosen according to KDIGO (2012) recommendation, such as: GFR more than 90 ml/min/1.73 cm2 – high or optimal, 60–89 ml/min/1.73 cm2 – slightly reduced, 45–59 ml/min/1.73 cm2 – moderately reduced, 30–44 ml/min/1.73 cm2 – vastly reduced, 1529 ml/min/1.73 cm2 – highly reduced, lower than 15 ml/min/1.73 cm2 – terminal renal failure. Results and discussion. Average GFR(CKD-EPI) level in all age groups was 99,9 ml/min/1.73 cm2 . Average GFR(CKD-EPI) was 104.41 ml/min/1.73 cm2 in 25–34 age group. Male average GFR(CKD-EPI) levels in appropriate age groups were reliably higher comparing to female levels. Both male and female analyzed indicators turned out to be reliably lower in older group than in the younger one. 95.1 % of male participants at the age from 25 to 34 years old had GFR ≥ 90 ml/min/1.73 cm2 , while female indicator was 76.9 %. The indicators in the age group from 35–45 years old were: for males – 86.4 %, for females – 58.3 %. Both male and female groups at the age from 35 to 45 contained people with GFR < 60.ml/min/1.73 cm2 (2 men – 0,8 %; 1 woman – 0.4 %). While GFR calculating according to MDRD and CKD-EPI formulas two dissimilar results were revealed. The advantages of CKD-EPI formulas calculating for higher GFR indicators have been evidenced.